Simulation of emission spectra of transition metal dichalcogenide monolayers with the multimode brownian oscillator model - Shen, Kaijun (2022)
The multimode Brownian oscillator model is employed to simulate the emission spectra of transition metal dichalcogenide (TMD) monolayers. Good agreement is obtained between measured and simulated photoluminescence spectra of WSe2, WS2, MoSe2, and MoS2 at various temperatures. The Huang-Rhys factor extracted from the model can be associated with that from the modified semiempirical Varshni equation at high temperatures. Individual mechanisms leading to the unique temperature-dependent emission spectra of those TMDs are validated by the multimode Brownian oscillator (MBO) fitting, while it is, in turn, confirmed that the MBO analysis is an effective method for studying the optical properties of TMD monolayers. Parameters extracted from the MBO fitting can be used to explore exciton-photon-phonon dynamics of TMDs in a more comprehensive model.